Kebijakan Pengembangan Ekowisata Mangrove Berkelanjutan untuk Konservasi Ekosistem dan Pemberdayaan Masyarakat Lokal - Nicha, Alvio; Zulkarnaini Zulkarnaini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the use of mangrove ecotourism as an integrative strategy for ecosystem conservation and improving the welfare of coastal communities. Using a qualitative approach with a case study method, data collection was conducted through in-depth interviews, field observations, and analysis of policy documents in several mangrove ecotourism locations in Indonesia. The research findings indicate that mangrove ecotourism ecosystems provide dual ecological and socio-economic impacts. From a conservation aspect, this model has succeeded in increasing community participation in mangrove rehabilitation and reducing environmental destruction activities. Economically, ecotourism creates livelihood diversification through various tourism-based businesses and mangrove derivative products. However, the study also identified major challenges in the form of: (1) ecological pressure from uncontrolled tourist visits, (2) equitable distribution of economic benefits, and (3) limited management capacity of local communities. This study recommends an integrated policy framework that includes: strengthening regulations based on environmental carrying capacity, collaborative management models, increasing community capacity, and fair benefit sharing mechanisms. The implementation of this sustainable policy is expected to optimize the role of mangrove ecotourism as a conservation tool as well as a driver of an inclusive local economy.